2018
DOI: 10.1038/s41426-018-0155-5
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic characterization and infectivity of a novel SARS-like coronavirus in Chinese bats

Abstract: SARS coronavirus (SARS-CoV), the causative agent of the large SARS outbreak in 2003, originated in bats. Many SARS-like coronaviruses (SL-CoVs) have been detected in bats, particularly those that reside in China, Europe, and Africa. To further understand the evolutionary relationship between SARS-CoV and its reservoirs, 334 bats were collected from Zhoushan city, Zhejiang province, China, between 2015 and 2017. PCR amplification of the conserved coronaviral protein RdRp detected coronaviruses in 26.65% of bats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
265
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 280 publications
(280 citation statements)
references
References 39 publications
11
265
0
4
Order By: Relevance
“…Moreover, bat-derived coronaviruses fell in basal positions in the subgenus Sarbecovirus, with 2019-nCoV most closely related to bat-SL-CoVZC45 and bat-SL-CoVZXC21, which were also sampled from bats. 23 These data are consistent with a bat reservoir for coronaviruses in general and for 2019-nCoV in particular. However, despite the importance of bats, several facts suggest that another animal is acting as an intermediate host between bats and humans.…”
Section: Sars-covsupporting
confidence: 76%
See 1 more Smart Citation
“…Moreover, bat-derived coronaviruses fell in basal positions in the subgenus Sarbecovirus, with 2019-nCoV most closely related to bat-SL-CoVZC45 and bat-SL-CoVZXC21, which were also sampled from bats. 23 These data are consistent with a bat reservoir for coronaviruses in general and for 2019-nCoV in particular. However, despite the importance of bats, several facts suggest that another animal is acting as an intermediate host between bats and humans.…”
Section: Sars-covsupporting
confidence: 76%
“…Some contigs identified in all the samples were closely related to the bat SARS-like betacoronavirus bat-SL-CoVZC45 betacoronavirus. 23 Bat-SL-CoVZC45 was then used as the reference genome and reads from each pool were mapped to it, generating consensus sequences corresponding to all the pools. These consensus sequences were then used as new reference genomes.…”
Section: Resultsmentioning
confidence: 99%
“…The bat CoV to which 2019_nCoV has the highest similarity was isolated from Rhinolophus sinicus (MG772933, described in Hu et al 2018), which might indicate that this species may also have been the original source of Figure 2 Phylogenetic tree of the 253 5'-end noncoding sequences of Sarbecovirus species from bats. A Merbecovirus was included as an outlier.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports showed that species from the bat genera Rhinolophus in southern China are a rich pool of SARS-like-CoVs, which belong to the subgenera Sarbecovirus. These viruses exhibit rich genetic diversity and frequent recombination events, which may increase the potential for cross-species transmission [7,42,[51][52][53][54][55]. Here, we reconstructed the evolutionary history of the 2019-nCoV cluster (Box Box 1.…”
Section: Trends In Molecular Medicinementioning
confidence: 99%